2015
DOI: 10.4103/0970-0358.163053
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism of bone morphogenetic protein 4 gene: A risk factor of non-syndromic cleft lip with or without palate

Abstract: Background:The bone morphogenetic protein (BMP) signalling pathway is crucial in a number of developmental processes and is critical in the formation of variety of craniofacial elements including cranial neural crest, facial primordium, tooth, lip and palate. It is an important mediator in regulation of lip and palate fusion, cartilage and bone formation.Aim:To study the role of mutation of BMP4 genes in the aetiology of non-syndromic cleft lip with or without palate (NSCL ± P) and identify it directly from hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Thus, a total of 11 eligible publications were finally included in the present meta-analysis. [ 13 15 , 19 – 26 ] The characteristics of the included studies are presented in Table 1 . Of these studies, seven were hospital-based case–control designs, and 4 were population-based case–control designs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a total of 11 eligible publications were finally included in the present meta-analysis. [ 13 15 , 19 – 26 ] The characteristics of the included studies are presented in Table 1 . Of these studies, seven were hospital-based case–control designs, and 4 were population-based case–control designs.…”
Section: Resultsmentioning
confidence: 99%
“…The genotype distribution in the control group was consistent with HWE in all studies except for one. [ 13 ]…”
Section: Resultsmentioning
confidence: 99%
“… 17 According to Rafighdoost et al, 18 in the population of southeastern Iran, the BMP4 rs17563 variant has a protective effect on the occurrence of NSCLP. In a separate case-control study by Savitha et al, 19 on NSCLP, one study reported an increased risk of NSCLP in Indian population.…”
Section: Discussionmentioning
confidence: 98%
“…The BMP4 rs17563 T>C was studied in a Chinese population 17 , where they find no significant association between BMP4 rs17563 T>C and orofacial cleft. Study in Karnataka, India, with a total sample of 200, 100 for each group shows that there was a significant difference with p < 0.05, OR = 4.2%.…”
Section: Discussionmentioning
confidence: 99%